Composing Media Composing Embodiment - Wysocki, Anne Frances, 1956-; Arola, Kristin L. (Book collections on Project MUSE., 2012)
"What any body is-and is able to do-cannot be disentangled from the media we use to consume and produce texts."--The Introduction. Kristin Arola and Anne Wysocki argue that composing in new media is composing the body-is embodiment. In Composing (Media) = Composing (Embodiment), they have brought together a powerful set of essays that agree on the need for compositionists-and their students-to engage with a wide range of new media texts. These chapters explore how texts of all varieties mediate and thereby contribute to the human experiences of communi